The Epoxidized Vietnam Rubber Seed Oil as a Secondary Plasticizer/Thermal Stabilizer in PVC Processing - Nguyen Thi Thuy; Vu Minh Duc; Nguyen Thanh Liem (International Journal of Polymer Science)
The epoxidized rubber seed oil (EeRSO) was a mixture of epoxidized triglyceride, and epoxidized methyl ester of free fatty acids was used as a secondary plasticizer for PVC. An increase in tensile properties was observed by substituting the 10 phr DOP plasticizer with the EeRSO in PVC formulation. A leaching test was performed in five media to evaluate the plasticizing effect. The sample weight increased slightly after soaking in water and 30 wt.% acetic solution, decreased slightly in 10 wt.% KOH solution, and reduced sharply and strongly in sunflower oil and n-hexane. The 10 phr EeRSO in PVC formulation has presented an improvement in migration, volatilization characteristics, and thermal property of PVC. After 72 hours of soaking in n-hexane, the shore A hardness of the EeRSO plasticized PVC sample increased by 14.5% while the PVC sample without EeRSO was blistered and its shore A hardness could not be measured. This was the clearest evidence for the positive effect of EeRSO as a secondary plasticizer. The morphology of the fractured surface of the samples after immersing in n-hexane was studied by using scanning electron microscopy. Thermogravimetric analysis showed the role of EeRSO in significant improvement in thermal stability. In general, EeRSO not only acts as a primary plasticizer to improve the migration, extraction, and volatilization characteristics but also contributes to the thermal stability of PVC.